2018
DOI: 10.4103/ijd.ijd_118_17
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of combined dermaroller and platelet-rich plasma versus dermaroller alone in acne scars and assessment of quality of life before and after treatment

Abstract: Background:Scarring due to acne is a frequently encountered problem in dermatological outpatient department. Microneedling has been a well-accepted modality for the treatment of atrophic acne scars. Platelet-rich plasma (PRP) is a newer option to investigate.Aims:The aims of this study were (1) to compare the efficacy of combined dermaroller and PRP therapy with dermaroller alone in facial acne scars and (2) to assess the psychosocial impact due to acne scars and its treatment.Methods:A total of 55 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 23 publications
2
30
1
9
Order By: Relevance
“…Although heterogeneity existed in the utilization of secondary outcomes, six of the eight trials used Goodman and Baron scores as the primary outcome. Two trials with an unclear risk of selective reporting used undocumented scales for primary outcome evaluation (Figure ) . While no studies reported a published protocol, there were no reporting discrepancies between methodology and results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although heterogeneity existed in the utilization of secondary outcomes, six of the eight trials used Goodman and Baron scores as the primary outcome. Two trials with an unclear risk of selective reporting used undocumented scales for primary outcome evaluation (Figure ) . While no studies reported a published protocol, there were no reporting discrepancies between methodology and results.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were either a comparative, simple randomized, noncontrolled study, 12,18,19 or a nonrandomized, controlled, beforeand-after study. 13,[20][21][22][23] The included study characteristics are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, PRP has gained traction in many different specialties including in dermatology where it is used to treat acne [102], scarring [103], and alopecia [104,105], in regenerative medicine where it is used to treat acute and chronic injuries to bone and cartilage [106,107], in orthopedics and sports medicine where it is used to treat rotator cuff tears, osteoarthritis of the knee, hamstring injuries, and Achilles tendinopathy [108][109][110], in dentistry where it is used during tooth extractions, periodontal surgery, and dental implant surgery [111,112], and more recently in wound healing to promote enhanced healing [113][114][115][116][117][118]. PRP is an autologous blood product generated from multiple rounds of centrifugation that serve to concentrate the number of platelets in plasma.…”
Section: The Use Of Polyp-containing Prp To Promote Wound Healing In mentioning
confidence: 99%
“…[ 35 ] In a study on 55 adult patients with atrophic acne scars, significantly better improvement and better dermatology life quality index (DLQI) scores were reported by the use of derma roller combined with PRP, compared with derma roller alone. [ 36 ]…”
Section: Prp In Dermatologymentioning
confidence: 99%